Gambaran Eritrosis Kerbau Karapan yang Diberi Latihan dengan Interval Berbeda (ERYTHROCYTE PROFILES OF EXCERCISING SWAMP BUFFALOES UNDER VARIOUS EXERCISE INTERVAL) - Dharmawan, Nyoman Sadra; Mahardika, I Gede (Jurnal Veteriner; Vol 1 No 1 (2000), 2016)
Gambaran Eritrosis Kerbau Karapan yang Diberi Latihan dengan Interval Berbeda (ERYTHROCYTE PROFILES OF EXCERCISING SWAMP BUFFALOES UNDER VARIOUS EXERCISE INTERVAL)
Keywords: erytrocyte; buffaloes; exercise